Autologous Bone Marrow Cell Infusion for the Treatment of Decompensated Liver Cirrhosis Patients With Type 2 Diabetes Mellitus - Liu, Baochi; Cheng, Mingrong; Lang, Lin; Li, Lei; Si, Yanhui; Wang, Guangmian (Frontiers in Physiology, 2021)
This study aimed to indicate whether autologous bone marrow cell infusion (ABMI) via the right omental vein (ROV) could have a regulatory effect on decompensated liver cirrhosis (DLC) patients with type 2 diabetes mellitus (T2DM). For this purpose, 24 DLC patients with T2DM were divided into treatment group (n=14) and control group (n=10). Patients in the treatment group were given ABMI through the ROV and right omental artery (ROA), and cases in the control group received ABMI through the ROV. At 1, 3, 6, and 12 months after ABMI, it was revealed that the prothrombin time, the total bilirubin levels, and the amount of ascites were significantly lower, while the serum albumin levels in the two groups were markedly higher compared with those before ABMI (P<0.01), and there was no significant difference between the two groups at each time point (P> 0.05). The fasting blood glucose and glycosylated hemoglobin levels at 6 and 12 months after ABMI in the two groups significantly decreased compared with those before ABMI (P<0.05 or <0.01), while the decreased levels in the treatment group were more obvious than those in the control group at each time point (P<0.01). The amount of insulin in the treatment group at 3, 6, and 12 months after ABMI was significantly less than that before ABMI in the control group (P<0.01). In summary, ABMI showed a significant therapeutic efficacy for DLC patients with T2DM through ROV and ROA. ABMI through ROV did not significantly improve diabetes, and ABMI though ROA did not enhance the liver function.